Penggunaan Distribusi Sampling Untuk Mengidentifikasi Kesenjangan Digital Berdasarkan Data Akses Digital - Chyntia Stefhany; Juwita Juwita; Universitas Palangka Raya (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The development of information and communication technology (ICT) has had a significant impact on global society, particularly in enhancing access to information, education, and economic opportunities. However, the digital divide remains a major issue, with large disparities in internet access between developed and developing countries. This study aims to identify the digital divide based on internet access data across countries using the sampling distribution method. The data used in this research was sourced from Kaggle and analyzed using Python to obtain an overview of the variability and average internet user percentages across different countries. The findings indicate a significant disparity in internet access, with developed countries enjoying near-universal access, while developing countries, particularly in sub-Saharan Africa and South Asia, face serious barriers to internet penetration. The sampling distribution analysis reveals a clear pattern of disparity, influenced by economic factors, government policies, and digital infrastructure readiness. This study suggests the need for improved technology infrastructure, internet access subsidies, and digital literacy training in countries with low internet penetration. With these measures, the digital divide can be reduced, supporting more inclusive and sustainable economic growth.